Deep sea corals off Brazil verify a poorly ventilated Southern Pacific Ocean during H2, H1 and the Younger Dryas - Mangini, Augusto; Godoy, J. M.; Godoy, M. L.; Kowsmann, R.; Santos, G. M.; Ruckelshausen, Mario; Schröder-Ritzrau, Andrea; Wacker, L. (Earth and planetary science letters, 2010)
Simultaneous 14C and Th/U dating of deep sea corals are useful for reconstructing the intensity of deep ocean circulation in the past, as they deliver the time between the gas exchange of the water with the atmosphere and the incorporation of the 14C in the carbonates (Adkins and Boyle, 1997; Adkins et al., 1998; Mangini et al., 1998). Th/U ages of deep sea corals sampled in sediment cores from locations off the coast of Brazil bathed by Antarctic Intermediate Water at depths between 600 and 800m group close to Heinrich events H2, H1 and the Younger Dryas. The Δ14C of the water bathing the corals starts to decrease approximately 2kyr before the Heinrich events and decreases to values 400‰ lower than the corresponding back tracked atmospheric values. The timing and the magnitude of the decrease is similar to that observed in intermediate water in the N. Pacific off Baja California (Marchitto et al., 2007) and in the Eastern Pacific (Stott et al., 2009). High ventilation ages, partly exceeding 4000years, are an unambiguous indication for a reduction of North Atlantic deep water formation during H2, H1 and the YD, as deduced from higher 231Pa/230Th activity ratios and from εNd in N. Atlantic Ocean sediments (McManus et al., 2004; Pahnke et al., 2008; Yu et al., 1996). They also could indicate a poorly oxygenated Southern Pacific Ocean at the end of the Heinrich events.